Pengaruh Pendapatan Pada Konsumsi Di Indonesia: Pengembangan Model Teoritis Dan Pemilihan Model Empiris - Manuati Dewi, Gusti ayu (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112)DO - 10.24843/JEKT.2015.v08.i01.p03, 2015)
The purpose of this study is to develop theoretical model and choose empirical model of the effect of income on consumption in Indonesia. By using secondary data of two macro economics indicators i.e Product Domestic Bruto and consumption, estimation of chosen model is analyzed through Partial Adjustment Model and Correction Error Model. The findings show that model with log-linear function is suitable for estimating the effect of consumption on income in Indonesia for data of 1980-2000. Additionally, the first model is superior to the second one for predicting consumption in association with income in this country.
Keywords: partial adjustment model, error correction model, consumption, income.